Strategi Madrasah Dalam Meningkatkan Partisipasi Masyarakat Pada Mutu Pendidikan - Moh. Sugeng (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2021)
MA Mamba'ul Ma'arif Banjarwati Paciran Lamongan is an educational institution whose geographical location is very good, therefore, marketing educational institutions have an advantage in promotion to be known by others. but there are various kinds of competitive challenges, the number of MA Ma'arif institutions in the Paciran Lamongan area, besides this geographical location which initially became an advantage turned out to be a challenge for the institution. The steps of data analysis, namely: data reduction, data display. Conclusion drawing and verification. The results of the study are as follows: Madrasah strategies in increasing community participation at MA Mamba'ul Ma'arif Banjarwati include: (1) Recommending teachers and students to promote institutions and people closest to them. (2) ethical approach. and the concept of kinship (3) Creating an MA image plus skills. The implementation of the Madrasah Strategy in increasing the participation of the MA Mamba'ul Ma'arif Banjarwati Community includes: (1) promotions (2) The existence of internships for class XI children (3) Selling accessories with institutional labels.